Weimar on the Pacific : German exile culture in Los Angeles and the crisis of modernism - Bahr, Ehrhard (Berkeley : University of California Press, 2007)
In the 1930s and '40s, LA became a cultural sanctuary for a distinguished group of German artists and intellectuals - including Thomas Mann, Theodor W. Adorno, Bertolt Brecht, Fritz Lang, and Arnold Schoenberg - who were fleeing Nazi Germany. This book is the first to examine their work and lives.
The dialectic of modernism -- Art and its resistance to society: Theodor W. Adorno's aesthetic theory -- Bertolt Brecht's California poetry: mimesis or modernism? -- The dialectic of modern science: Brecht's Galileo -- Epic theater versus film noir: Bertolt Brecht and Fritz Lang's anti-Nazi film Hangmen also die -- California modern as immigrant modernism: architects Richard Neutra and Rudolph M. Schindler -- Between modernism and antimodernism: Franz Werfel -- Renegade modernism: Alfred Döblin's novel Karl and Rosa -- The political battleground of exile modernism: the Council for a Democratic Germany -- Evil Germany versus good Germany: Thomas Mann's Doctor Faustus -- A "True Modernist": Arnold Schoenberg -- Conclusion: The Weimar legacy of Los Angeles.
Includes bibliographical references (p. 323-346) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Modernism (Aesthetics) -- California -- Los Angeles; Germans -- California -- Los Angeles -- Intellectual life; Jews, German -- California -- Los Angeles -- Intellectual life; Los Angeles (Calif.) -- Intellectual life -- 20th century; Modernisme (Esthétique) -- Californie -- Los Angeles; Allemands -- Californie -- Los Angeles -- Vie intellectuelle; Juifs allemands -- Californie -- Los Angeles -- Vie intellectuelle; Los Angeles (Calif.) -- Vie intellectuelle -- 20e siècle.; HISTORY -- United States -- State & Local -- West (AK, CA, CO, HI, ID, MT, NV, UT, WY); Modernism (Aesthetics) -- California -- Los Angeles; Germans -- California -- Los Angeles -- Intellectual life; Jews, German -- California -- Los Angeles -- Intellectual life; Los Angeles (Calif.) -- Intellectual life -- 20th century; Intellectual life; Germans -- Intellectual life; Jews, German -- Intellectual life; Modernism (Aesthetics); California -- Los Angeles; Literatur; Exil; Geistesleben; Weimarer Republik; Exilschriftsteller; Los Angeles, Calif; Kalifornien; Deutschland; Deutsche; 1900-1999; 18th century; 1930s.; 1940s.; 20th century; american history; arnold schoenberg; bertolt brecht; california; classicism; ehrhard bahr; exile; fritz lang; german artists; german modernism; germany; intellectual; los angeles; modernism; national socialism; pacific coast; schoenberg; socialism; southern california; theodore adorno; thomas mann; united states history; us history; weimer germany; weimer republic; west coast; western united states